Роль белки обыкновенной (Sciurus vulgaris L.) в расселении грецкого ореха - Свириденко, П.А. (Вестник зоологии, 1971)
Observations in the Kiev environs showed that Sciurus vulgaris L. provide themselves with walnuts, burring them into a loose soil (dug up places or soil loosen by a mole)
one by one at a depth of 6—8 cm. S. vulgaris is good in finding the places of walnut burring and uses the reserves in autumn, spring and probably in winter with a loose snow cover. S. vulgaris always burries only big walnuts, those not used by it, sprout.
It was established by experiments that of all the forest rodents, besides S. vulgaris,
only Glis glis L. is capable of crocking and breaking the nut shell. Glis glis L. however,
does not bury its reserves into the soil, does not eat the walnuts. S. vulgaris is a single natural distributer of the walnut.